Truck seating comfort: objectify and subjectify measurement approach - Tan, CheeFai; Sarban Singh, Ranjit Singh; Siti Aisyah, Anas (2011)
Technology has changed trucks significantly over the years. Truck companies are getting interested in comfortable equipment for their employees in order to create a healthy and stimulating working environment. Due to this reason, truck manufacturers recognize comfort as one of the major selling point, as it is thought to play an important role for the buyer as well. Seat is one of the most important components of truck and they are the place where professional driver spend most of their time. The aim of the paper is to describe the measurement methods that used to improve the physiological comfort of truck driver’s seat. There will be three sections in the paper. First, the paper describes the nature of sitting comfort and discomfort. Secondly, it describes the subjective and objective measurement methods that are used to evaluate the truck seat. Thirdly, the paper proposes a methodology for the development of comfortable truck driver’s seats.